2002
DOI: 10.1093/nar/gkf434
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of DNA demethylation and transcriptional reactivation of the FMR1 gene in fragile X cells treated with 5-azadeoxycytidine

Abstract: In fragile X syndrome, hypermethylation of the expanded CGG repeat and of the upstream promoter leads to transcriptional silencing of the FMR1 gene. Absence of the FMR1 protein results in mental retardation. We previously proved that treatment with 5-azadeoxycytidine (5-azadC) of fragile X cell lines results in reactivation of the FMR1 gene. We now show that this treatment causes passive demethylation of the FMR1 gene promoter. We employed the bisulfite-sequencing technique to detect the methylation status of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
89
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 35 publications
15
89
1
Order By: Relevance
“…However, HDAC inhibitors alone were unable to induce any reactivation at all [Chiurazzi et al, 1999], suggesting that DNA methylation is dominant over histone hypoacetylation at the FMR1 locus, as also reported for other heavily methylated genes [Cameron et al, 1999]. These initial observations were confirmed by measuring FMR1 transcript with real-time RT-PCR and confirming DNA demethylation at the FMR1 promoter after 5-azadC treatment [Pietrobono et al, 2002]. We then investigated histone modifications in the promoter, exon 1 and exon 16 of FMR1 by chromatin immunoprecipitation (ChIP) before and after pharmacological treatment of FXS lymphoblasts with 5-azadC and acetyl-L-carnitine .…”
supporting
confidence: 68%
See 1 more Smart Citation
“…However, HDAC inhibitors alone were unable to induce any reactivation at all [Chiurazzi et al, 1999], suggesting that DNA methylation is dominant over histone hypoacetylation at the FMR1 locus, as also reported for other heavily methylated genes [Cameron et al, 1999]. These initial observations were confirmed by measuring FMR1 transcript with real-time RT-PCR and confirming DNA demethylation at the FMR1 promoter after 5-azadC treatment [Pietrobono et al, 2002]. We then investigated histone modifications in the promoter, exon 1 and exon 16 of FMR1 by chromatin immunoprecipitation (ChIP) before and after pharmacological treatment of FXS lymphoblasts with 5-azadC and acetyl-L-carnitine .…”
supporting
confidence: 68%
“…2), effectively transforming a methylated full mutation into an unmethylated full mutation (UFM) Tabolacci et al, 2008a]. 5-azadC effects increased with dose and treatment time [Chiurazzi et al, 1999;Pietrobono et al, 2002], but 4 weeks after treatment was discontinued we observed regain of DNA methylation in the FMR1 promoter and loss of transcription [Pietrobono et al, 2002]. Further follow-up experiments are war-ranted in order to understand if some clones actually remained demethylated or if all cells reverted to the heterochromatic status.…”
Section: Transcriptional Therapy Of Fragile X and Other "Epigenetic" mentioning
confidence: 85%
“…However, even though epigenetic states are potentially reversible, treatment with agents generally affecting DNA methylation have their natural limitation due to their non-selectivity and sometimes also because of their inefficiency to demethylate particular CpG sequences. 41,42 Moreover, simultaneous change of a whole network of epigenetically silenced genes by inhibitory drugs may negatively interfere with the final outcome of a proper immunological response. 43 In fact, preincubation with sodium butyrate did not unmask those cells selected by our method (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The FMR1 amplicon is a 89-bp product spanning the junction between exon 13 and 14 of the gene (positions 1432 -1520 of GenBank sequence NM_002024). The primers and TaqMan probe employed were as described by Pietrobono et al 33 The relative amount of FMR1-mRNA was assessed by comparison with the human HPRT-mRNA detected with the Pre-Developed TaqMan Assay Reagent (ABI 4310890E: huHPRT endogenous control).…”
Section: Methodsmentioning
confidence: 99%